2016
DOI: 10.1007/s10802-016-0128-x
|View full text |Cite
|
Sign up to set email alerts
|

Single Mother Parenting and Adolescent Psychopathology

Abstract: Children raised in single-mother families are at increased risk for psychopathology, but the mechanisms that help explain this relationship are understudied. In a community sample of diverse adolescents (N= 385, 52% female, 48% Caucasian) and their mothers, we hypothesized that single mothers would be more likely than cohabitating mothers to engage in negative parenting behaviors, which would predict adolescent psychopathology prospectively. Single mothers were more likely to engage in psychologically controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 64 publications
3
61
1
Order By: Relevance
“…Although highly correlated, the association between single-parent household and depressive symptoms remained after taking public assistance into account (Table 3, Model III). Prior studies have also shown these indicators to play a major part in the increased risk of depression (Amato and Keith, 1991; Duncan and Brooks-Gunn, 1997; Weitoft et al, 2003; McLanahan and Sandefur, 1994; Daryanani et al, 2016). A large-scale Swedish study examining mortality and morbidity in children with single parents showed that, although growing up in a single-parent family often is associated with a wide range of other social adversities including lack of household resources the increased risk of mental health problems for children of single parents remained even after taking other adversities into account (Weitoft et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although highly correlated, the association between single-parent household and depressive symptoms remained after taking public assistance into account (Table 3, Model III). Prior studies have also shown these indicators to play a major part in the increased risk of depression (Amato and Keith, 1991; Duncan and Brooks-Gunn, 1997; Weitoft et al, 2003; McLanahan and Sandefur, 1994; Daryanani et al, 2016). A large-scale Swedish study examining mortality and morbidity in children with single parents showed that, although growing up in a single-parent family often is associated with a wide range of other social adversities including lack of household resources the increased risk of mental health problems for children of single parents remained even after taking other adversities into account (Weitoft et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As research has consistently identified single motherhood as a risk factor for youth depression (Daryanani et al, 2016; Hilton & Devall, 1998), it is important to understand why children of single mothers are at greater risk for depression than children of partnered mothers. The results of our analyses indicate that youth raised in single-mother families are at increased risk for depression due, in part, to engaging in more ruminative processes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this postulate, stressful life events are experienced more regularly, and interpreted as more impactful, during adolescence, with much research concluding that elevated stress is a prominent risk factor for adolescent depression (e.g., Hamilton et al, 2013). As children of single mothers are at risk for chronic stressors before the onset of adolescence (Daryanani et al, 2016; Lipman et al, 1997), it would likely take less additional stressors during adolescence to compromise a child’s ability to adequately cope, which in turn puts them at earlier risk for depression than adolescents from two-parent families. We found partial support for this theory, as our analyses revealed that stressful events during childhood were more common among adolescents of single mothers and predicted elevated rumination, although there was only trending significance of childhood stressors as a mediator of this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations